Tuberculosis: A granulomatous disease mediated by epigenetic factors. (July 2020) - Batista, Letícia Avelino Ferreira; Silva, Káifer José Soares; da Costa e Silva, Letícia Marques; de Moura, Yasmin Ferreira; Zucchi, Fabíola Cristina Ribeiro
Abstract: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, which is transmitted via aerosol. TB is a secular fatal disease which still represents a health problem worldwide. TB has long incubation period and usually at first, affects the lungs. However, the infection could also attack other organs including lymph nodes, abdomen, genitourinary tract, skin, joints, bones and nervous system, what are known as extrapulmonary TB (EPTB). The granulomatous lesions are characterized by necrosis and liquefaction, which causes several lungs damages. Granulomas have traditionally been known to be protective host structures, but mycobacteria can use granuloma as vehicle for expansion by intercellular spread, and it might facilitate M. tuberculosis dissemination to other body areas. Hypoxia, which occurs in granuloma areas contribute to disease progression, as the bacilli adapt to lack of oxygen and low nutrient concentration leading to modulation of angiogenesis genes expression. Induction of angiogenesis has controversial actions, while it could benefit the host by providing a direct source for the arrival of immune system cells against a pathogen, this conditions can also promote bacterial growth and spread to other tissues. This occurs due a greater supply of oxygen and nutrients. Epigenetic processes, such as miRNAs fluctuations, modulate angiogenesis resulting in pathogen mediated interference in angiogenic processes. M. tuberculosis infection affects microRNA expression profile in host tissues. Several miRNAs are involved in cell development, proliferation, differentiation, apoptosis, and even anti-inflammatory and pro-inflammatory stimuli. MicroRNAs promote dual role on M. tuberculosis infection, persistence, and host immune system modulation. These molecules might represent great potential as biomarkers of disease progression, spread, activity, and latency. The purpose of this review is to discuss how epigenetic mechanisms can influence the spread of Mycobacterium tuberculosis, affecting the expression of mediators of angiogenesis, the formation of granuloma, and the installation of the disease.